Some properties of n-isoclinism in Lie algebras - Parvaneh, Foroud; Moghaddam, Mohammad Reza R.; Khaksar, A. (Italian Journal of Pure and Applied Mathematics, 2011)
In 1940, P. Hall introduced the concept of isoclinism of groups and it was generalized to n-isoclinism and isologism with respect to a given variety of groups. In the present article this notion is studied in Lie algebras and give some results similar to N.S. Hekster in 1986. In particular, it is shown that every family of n-isoclinism of Lie algebras contains an n-stem Lie algebra of minimal dimension.